Removal and identification of external protein corona members from RBC‐derived extracellular vesicles by surface manipulating antimicrobial peptides. Issue 3 (8th March 2023) - Singh, Priyanka; Szigyártó, Imola Cs.; Ricci, Maria; Gaál, Anikó; Quemé‐Peña, Mayra Maritza; Kitka, Diána; Fülöp, Lívia; Turiák, Lilla; Drahos, László; Varga, Zoltán; Beke‐Somfai, Tamás
Abstract: In the last years, extracellular vesicles (EVs), secreted by various cells and body fluids have shown extreme potential in biomedical applications. Increasing number of studies suggest that a protein corona could adhere to the surface of EVs which can have a fundamental effect on their function, targeting and therapeutical efficacy. However, removing and identifying these corona members is currently a challenging task to achieve. In this study we have employed red blood cell‐derived extracellular vesicles (REVs) as a model system and three membrane active antimicrobial peptides (AMPs), LL‐37, FK‐16 and CM15, to test whether they can be used to remove protein corona members from the surface of vesicles. These AMPs were reported to preferentially exert their membrane‐related activity via one of the common helical surface‐covering models and do not significantly affect the interior of lipid bilayer bodies. The interaction between the peptides and the REVs was followed by biophysical techniques, such as flow‐linear dichroism spectroscopy which provided the effective applicable peptide concentration for protein removal. REV samples were then subjected to subsequent size exclusion chromatography and to proteomics analysis. Based on the comparison of control REVs with the peptide treated samples, seventeen proteins were identified as external protein corona members. From the three investigated AMPs, FK‐16 can be considered as the best candidate to further optimize EV‐related applicability of AMPs. Our results on the REV model system envisage that membrane active peptides may become a useful set of tools in engineering and modifying surfaces of EVs and other lipid‐based natural particles. Abstract :